2018
DOI: 10.1016/j.mri.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and reducing the effects of confounding factors for robust T1 and T2 mapping with cardiac MR fingerprinting

Abstract: This study aims to improve the accuracy and consistency of T and T measurements using cardiac MR Fingerprinting (cMRF) by investigating and accounting for the effects of confounding factors including slice profile, inversion and T preparation pulse efficiency, and B. The goal is to understand how measurements with different pulse sequences are affected by these factors. This can be used to determine which factors must be taken into account for accurate measurements, and which may be mitigated by the selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
119
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(138 citation statements)
references
References 34 publications
15
119
4
Order By: Relevance
“…Accurate water T 1 and T 2 values were obtained with the proposed approach in comparison to spin echo‐based reference values (R 2 > 0.99, NRMSE T1 = 1.4% and NRMSE T2 = 5.4%). A slice profile correction was included in the dictionary to obtain accurate measurements (for T 2 especially) when using short pulses . A Bloch simulation of the inversion efficiency was also included, impacting mainly the T 1 measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate water T 1 and T 2 values were obtained with the proposed approach in comparison to spin echo‐based reference values (R 2 > 0.99, NRMSE T1 = 1.4% and NRMSE T2 = 5.4%). A slice profile correction was included in the dictionary to obtain accurate measurements (for T 2 especially) when using short pulses . A Bloch simulation of the inversion efficiency was also included, impacting mainly the T 1 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Inversion pulses are applied every 5 heartbeats with delays of [10, 300, 10] ms, whereas T 2 preparations with TEs of [No T 2 prep, No T 2 prep, 40, 80, 160] ms are repeated 3 times over the 15 heartbeats. Additional contrast encoding is provided with the flip angle pattern composed of a linear ramp‐up of 20 RF pulses from 5° to 30° followed by a fixed 30° flip angle . Low flip angles, fixed TR and gradient spoiling were used to reduce the signal’s sensitivity to B 0 and B 1 inhomogeneities .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 3 T, myocardial T 1 values between 1477 and 1569 ms have been reported with SASHA . In this study, the cMRF dictionary included corrections for some confounding factors that could introduce quantitative errors if not taken into account . Specifically, the dictionary simulation modeled both the non‐ideal slice profile, and T 1 and T 2 relaxation during the inversion and T 2 preparation pulses.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, magnetization transfer effects are not taken into account. No B 1 + corrections were performed, although previous work has shown that this particular cMRF sequence is relatively robust to B 1 + variations . The slice profile correction that was included in the dictionary assumes there is only one tissue type across the slice direction of each voxel, and it does not consider partial volume or multi‐compartment effects.…”
Section: Discussionmentioning
confidence: 99%